Consumer construal of separation in virtual services. Issue 2 (13th March 2017) - Hartley, Nicole; Green, Teegan
Abstract : Purpose: Service encounters are becoming increasingly virtual through the infusion of computer-mediated technologies. Virtual services separate consumers and service providers both spatially and temporally. With the advent of virtual services is the need to theoretically explain how service separability is psychologically perceived by consumers across the spectrum of computer-mediated technologies. Drawing on construal-level theory, the purpose of this paper is to conceptualize a theoretical framework depicting consumer's construal of spatial and temporal separation across a continuum of technology-mediated service virtuality. Design/methodology/approach: The authors conducted two studies: first, to investigate consumers' levels of mental construal associated with varying degrees of service separation across a spectrum of technology-mediated services; second, to empirically examine consumer evaluations of service quality in response to varying degrees of spatial and temporal service separation. These relationships were tested across two service industries: education and tourism. Findings: Consumers mentally construe psychological distance in response to service separation and these observations vary across the spectrum of service offerings ranging from face-to-face (no psychological distance) through to virtual (spatially and temporally separated – high psychological distance) services. Further, spatial separation negatively affects consumers' service evaluations; such that as service separation increases, consumers' service evaluations decrease. No such significant findings support the similar effect of temporal separation on customer service evaluations. Moreover, specific service industry-based distances exist such that consumers responded differentially for a credence (education) vs an experiential (tourism) service. Originality/value: Recent studies in services marketing have challenged the inseparability assumption inherent for services. This paper builds on this knowledge and is the first to integrate literature on construal-level theory, service separability, and virtual services into a holistic conceptual framework which explains variance in consumer evaluations of separated service encounters. This is important due to the increasingly virtual nature of service provider-customer interactions across a diverse range of service industries (i.e. banking and finance, tourism, education, and health care). Service providers must be cognisant of the psychological barriers which are imposed by increased technology infusion in virtual services.